In silico binding affinity to cyclooxygenase-II and green synthesis of benzylpyrazolyl coumarin derivatives. Issue 122 (24th November 2015) - Saha, Arijit; Payra, Soumen; Verma, Sant Kumar; Mandal, Mou; Thareja, Suresh; Banerjee, Subhash
Abstract : Here, we have reported enhanced molecular binding affinities of benzylpyrazolyl coumarin scaffolds with COX-II inhibitor and an ionic liquid catalyzed simple green synthetic route to access these scaffolds. Abstract : Here, we have reported for the first time, in silico binding affinity prediction of benzylpyrazolyl coumarin scaffolds to cyclooxygenase-II (COX-II) enzyme and a green synthetic route to access these scaffolds using a neutral ionic liquid, [pmIm]Br as the reusable catalyst and reaction media under metal-free conditions. The integrated scaffolds, benzylpyrazolyl coumarins exhibited stronger binding affinity to COX-II inhibitor than their individual moieties, 3-benzyl coumarins and pyrazolones. Moreover, 4-((4-hydroxy-2-oxo-2 H -chromen-3-yl)(4-nitrophenyl)methyl)-5-methyl-2-phenyl-1 H -pyrazol-3(2 H )-one (3c ) has shown even better binding affinity than the marketed anti-inflammatory drug, celecoxib.